Musculoskeletal diseases caused by ergonomic agents on workers affiliated to the Mexican Institute of Social Security, Mexico - Franco Chavez, Sergio Adalberto; Salazar Páramo, Mario; Peña Ortiz, Maria Olivia; Aguilera Velasco, María de los Angeles (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2017)
Musculo-skeletal diseases (MSDs) present serious health issues. Objective: identify the prevalence of musculo-skeletal disorders among workers registered in the Mexican Institute of Social Security (IMSS), México during the 2012-2014 period. This was a quantitative, retrospective and comparative research. Results: According to statistical data from the IMSS, MSDs distribution was as follows: De Quervain's radial tenosynovitis, the most frequent illness, 58 cases, followed by carpal tunnel syndrome with 46 cases; enthesopathies 39 cases and less frequently, shoulder lesions 25 cases and epicondylitis 11 cases. Conclusion: Having occupational health specialists is a must to reduce the risk of MSDs.